Domestic Remittances and Household Food Diversity in Rural Ghana - Baah-Kumi, Bernard; Lee, Yu-Feng (Journal of Social Economics Research, 2021)
This work investigates the effect of domestic remittances on households’ food diversity in rural Ghana using three-stage least squares estimation technique and cross-sectional data from the Ghana Living Standards Survey, round six (GLSS 6). The study finds that Northern Ghana rural households’ food diversity scores are lower than their Southern counterparts. Results show that domestic remittances positively affect rural household food diversity in Ghana, and the difference in food diversity index between Northern and Southern rural households narrows as remittances increase. The study also finds that rural households with at least primary educated householders have enhanced food consumption in variety while increasing household size tends to deteriorate food diversity. The study recommends that domestic remittances matter to food consumption diversity, especially in Northern Ghana. Therefore, policymakers should implement remittance tax credits to service providers and strengthen competition in the industry by supporting remittance technologies’ interoperability to minimize costs to increase flows. Increased domestic remittance flows to Northern Ghana could narrow the rural household food diversity gap between Northern and Southern Ghana. Farm and non-farm investment and rural sector-specific education investment are also recommended.